Female Community Health Volunteers’ (FCHVs) Involvement in Improving Maternal Health, Nepal - Shahi, Prakash (Journal of Karnali Academy of Health Sciences, 2019)
Improving maternal health was one of the eight millennium development goals (MDGs) in 2000 and later included in SDG as a major agenda in 2015 which was adopted by the international community.  In Nepal, the first elected democratic government developed Health Policy in 1991 and revised in 2014 which has identified safe motherhood as a priority program and institutionalized safe motherhood as a primary health care. In order to effectively address maternal and neonatal morbidity and mortality, the Family Health Division, Department of Health Services (DoHS) developed National Safe Motherhood Long Term Plan 2002- 2017 (revised in 2006) which aimed to establish basic and comprehensive emergency obstetric care services in all districts. To complement this plan, the National Policy on SBA (2006) was developed with the aim of increasing the percentage of births assisted by a skilled birth attendant (as internationally defined) to 60 percent by 2015. Table 1 explains some historical shifts in maternal health policies and programs in Nepal.